Disharmonisasi Pengaturan Pengelolaan Wilayah Izin Usaha Pertambangan Khusus bagi Organisasi Masyarakat Keagamaan di Indonesia - Egi Rivaldi Gumilar; Rianda Dirkareshza (Jurnal Interpretasi Hukum, 2024)
Exploration of mining wealth is an effort to accelerate the economy. Polemics arise when PP 25/2024 and Perpres 76/2024 are juxtaposed with positive law in the form of laws that have a higher hierarchical position. The three religious community organizations that have received WIUPK concession offers are Nahdlatul Ulama, Muhammadiyah, and Persatuan Islam. Mining concessions are often wrapped in political nuances, even allegedly ridden by the interests of certain groups. Leading to a number of controversies that arise, it is interesting to discuss the regulation of special mining business permit areas for religious community organizations in Indonesia and related to efforts to harmonize laws and regulations regarding the management of special mining business permit areas for religious community organizations as a concrete step to realize people's welfare. This research is qualitative and juridical-normative type. The research approach used is conceptual and legislation. The enactment of PP 25/2024 is a responsive effort accommodated by the government regarding the WIUPK arrangement. The issuance of Perpres 76/2024 states that WIUPK is a former PKP2B area that is given priority to religious mass organizations in order to promote community welfare. However, there are a number of risks that the involvement of religious community organizations could potentially result in conflicts of interest and have a negative impact on social and environmental balance. Despite normative controversy, this policy distributes benefits and provides access to natural resources previously controlled by large entities. Concrete steps that can be taken are harmonizing applicable regulations, such as revising the Minerba Law and the Ormas Law, or drafting inclusive and specific implementing regulations. Thus, religious community organizations can understand the technical, economic, and socio-environmental aspects of mining management, and are able to be responsible for realizing people's welfare.